Keberpihakan kepada Kaum Miskin: Tafsir Ideologi Ulangan 15:1-11 - Edward Jakson Turalely; Jafet Damamain; Margaretha Martha Anace Apituley (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2023)
Poverty was a crucial issue in the whole of human history, including in Old Testament times. One of the PL texts that shows this fact is Deuteronomy 15: 1-11. Deuteronomy 15: 1-11 contains the law of abolishing debts that must be carried out every seven years. This article then becomes the goal of conducting a search using the method of ideological interpretation. Based on his findings, it is known that the law of debt relief is an ideology that is sought as a counterpoint to the Deuteronomy source against the ideology of imposition which is the dominant mode of society's production. Through the idea of abolishing debt, the right to life of the poor is fought for. This understanding gave birth to an awareness of the importance of churching with the poor. All components are called upon to understand that GOD is on the side of the poor and then express it in the reality of life which is increasingly threatened.